HUBUNGAN HARGA DIRI DENGAN PERILAKU AGRESIF ANAK USIA 4-6 TAHUN DI TK TAMAN RAUDAH KECAMATAN TAMPAN KOTA PEKANBARU - Yasyintha Hulfah; Devi Risma; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the relationship between self-esteem and aggressive behavior of children aged 4-6 years in TK Raudah Park, Tampan District, Pekanbaru City. Where lack of knowledge on how to educate children well also occurs in parents who have children behaving aggressively, so that participation and supervision of parents in child development is not optimally stimulated. As for the number of population in this study were 60 children at 4-6 years of age, with samples 60 children used saturated samples. The method used was Person Product Moment correlation to see the relationship between self-esteem variables and aggressive behavior. Data collection techniques are observation sheets using a Likert Scale. The data analysis technique uses a scale trial and statistical method analysis with the SPSS for Windows program ver. 25. Based on the hypothesis test obtained there is a negative and significant relationship between self-esteem and aggressive behavior of children aged 4-6 years in TK Raudah Park, Tampan District, Pekanbaru City. This can be seen from the value of correlation coefficient of rxy = -0.315 and the significance level of 0.000 <0.05. The level of relationship between self-esteem and aggressive behavior is included in the strong category with a value of determination coefficient of 99%, meaning that self-esteem has an effect of 99% of aggressive behavior.Key Words: Self-Esteem, Aggressive Behavior.